Crossing boundaries : investigating human-animal relationships - Birke, Lynda I. A.; Hockenhull, Jo (Human-animal studies., 2012)
Many people feel strong bonds with nonhuman animals, and these relationships are central to much emerging scholarship in human-animal studies. Yet to study relationships is not straightforward; research often focuses on how humans affect animals or vice versa rather than on the relationships themselves. Partly, this is a consequence of the history of disciplinary divisions, particularly between natural and social sciences. In this book, contributors from a wide range of disciplinary backgrounds reflect on the methodological challenges they face, and how they go about studying relationships between people and animals. The book provides fascinating insights into how research on human-animal relationships can rise to the challenges of interdisciplinarity, and help us to understand the animals with whom we bond.